Prevalence of emphysema in people living with human immunodeficiency virus in the current combined antiretroviral therapy era: A systematic review - Ringheim, Hedda; Thudium, Rebekka F.; Jensen, Jens-Ulrik S.; Rezahosseini, Omid; Nielsen, Susanne D. (Frontiers in Medicine, 2022)
Before introducing combination antiretroviral therapy (cART), a higher prevalence of emphysema in people living with HIV (PLWH) than in the background population was reported. This systematic literature review aimed to investigate the prevalence of emphysema in PLWH and to compare the prevalence between PLWH and controls in the current cART era. A systematic literature search was conducted in PubMed, EMBASE, Scopus, and Web of Science (WOS), searching for “HIV” and “emphysema” from 1 January 2000 to 10 March 2021. Eligible studies were published after the introduction of cART, included PLWH, and reported the prevalence of emphysema. A total of 17 studies were included, and nine studies also included controls. The weighted average prevalence of emphysema in PLWH was 23% (95%CI: 16-30). In studies including both PLWH and controls the weighted average prevalence were 22% (95%CI: 10-33) and 9.7% (95%CI: 2.3-17), respectively (p=0.052). The prevalence of emphysema in never-smoking PLWH and controls just was reported in one study and was 18% and 4%, respectively (p<0.01). Thirteen of the studies had a moderate risk of bias, mainly due to selection of patients. A tendency to higher prevalence of emphysema was found in PLWH in comparison to controls in the current cART era. However, in the included studies, the definition of emphysema varied largely. Thus, to have a clear overview of the prevalence, further studies with well-designed cohorts of PLWH and controls are warranted.